Looking for a Place : Children's Guide - Ladd, Gretchen; Mittler, Sally (Santa Fe : SITE Santa Fe, 1999)
Almeida, Helena ; Antoni, Janine ; Bourgeois, Louise ; Cai Guo-Qiang ; Clark, Lygia ; Gatev, Dr. Galentin ; Hatoum, Mona ; Hausswolff, Carl Michael von ; Höller, Carsten ; Kaern, Simone Aaberg ; Mthethwa, Zwelethu ; Neshat, Shirin ; Neuenschwander, Rivane ; Sangar, Bülent ; Teters, Charlene ; Vega, Sergio ; Yanagi Miwa
Looking for a Place : The Third International Biennial, SITE Santa Fe, July 10 - December 31, 1999
Engels
boek